Climate Aridity under Changing Conditions and Implications for the Agricultural Sector: Italy as a Case Study. (20th December 2012) - Salvati, Luca; Zitti, Marco; Di Bartolomei, Rosanna; Perini, Luigi
Abstract : A comprehensive diachronic analysis (1951–2010) of precipitation and temperature regimes has been carried out at the national and regional scale in Italy to investigate the impact of climate aridity on the agricultural system. Trends in climate aridity have been also analysed using UNEP aridity index which is the ratio between rainfall and potential evapotranspiration on a yearly basis. During the examined time period, and particularly in the most recent years, a gradual reduction in rainfall and growing temperatures have been observed which have further widened the gap between precipitation amounts and water demand in agriculture.